"Because I'm Light Skin . . . They Think I'm Italian": Mexican Students' Experiences of Racialization in Predominantly White Schools. (April 2017) - Fergus, Edward
Discussions on Latino/a students' interpretation of the opportunity structure and schooling treat racial/ethnic identification among Latino/as as static, despite skin color variation. This article provides findings from interviews with six Mexican students who discussed teachers identifying them as "White-looking" or "Hispanic/Mexican-looking." Both groups shared belief in the achievement ideology and understood the opportunity structure as fraught with barriers. However, the "White-looking" students perceived themselves as being able to permeate such barriers meanwhile the "Hispanic/Mexican-looking" students believed such barriers affect their ability to "make it" regardless of their aspirations. This study raises questions regarding theories on academic variability of Latino/a students.